Juridical Analysis of the Judges Decision on Premature Lawsuit in the Settlement of Termination of Employment Problems (Case Study of Judge's Decision Number 1228 K/Pdt.Sus-Phi/2023) - Wika Setya Bhara; Shariffuddin, Nur Dinie (Indonesian Journal of Labour Law and Industrial Relations, 2024)
Hepin Situmorang is a former employee who worked at Martha Friska Hospital with a 17-year work period. The termination of employment carried out by PT Karya Utama Sejahtera and Martha Friska Hospital to Hepin Situmorang did not pay Severance Pay, Long Service Award Money and Replacement Money for Rights. Hepin Situmorang objected but there was no response from the hospital, so the mediation negotiations were continued with the Mediator at the Medan City Manpower Office. When no agreement was reached during the mediation, the mediator issued a recommendation for Martha Friska Hospital to pay Severance Pay. However, RS. Martha Friska and PT. Karya Utama Sejahtera did not implement the contents of the recommendation, so Hepin Situmorang filed this lawsuit in accordance with applicable legal provisions. Then Hepin Situmorang brought this problem to the Medan Industrial Relations Court, but the lawsuit filed by Hepin Situmorang was rejected at the time of the exception because PT. Karya Utama Sehat Sejahtera must also participate in bipartite negotiations and mediation because of the involvement of the parties in the main dispute, so that all parties have the same opportunity and space to prove who is the party obliged to pay Hepin Situmorang's rights. Dissatisfied with the decision issued by the Medan Industrial Relations Court, Hepin Situmorang filed an appeal. The result of the cassation decision accepted the lawsuit filed by Hepin Situmorang on the grounds that Martha Friska Hospital is a single entity with PT. Karya Utama Sehat Sejahtera and cannot be separated.